THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN SHAPING THE RELIGIOUS CHARACTER OF STUDENTS AT NAHDATUL ULAMA PRIVATE MADRASAH IBTIDAIYAH (MIS NU) RAO-RAO DOLOK VILLAGE - Sahrul Mukhlis Lubis; Risnawati; Miftahir Rizqa (RADJA PUBLIKA, 2024)
The role of an Islamic religious education teacher is a set of duties and responsibilities that must be carried out in their position as an educator. And the aim of this research is to find out the role of Islamic religious education teachers in shaping the religious character of students, to find out the inhibiting and supporting factors for Islamic religious education teachers in shaping the religious character of students at Madrasah Ibtidaiyah Nahdatul Ulama (MIS NU) in Rao Village. Rao Dolok. The method used in this research is a qualitative descriptive analysis technique, namely comparing the results obtained with standards that have been used previously. Then in this research, the presentation of data or a collection of structured information that provides the possibility for interest and taking action is presented, among other things, in the form of narrative text. The aim is to make it easier to read, understand and draw conclusions. The results of this research show that the role of Islamic religious education teacher is as an educator, as a teacher, as a guide and as a trainer. Meanwhile, inhibiting and supporting factors include: inhibiting factors, which influence the formation of religious character, including family and society. And supporting factors, by guiding students to develop more positively and instill religious values.